A Methodology for Cognitive NoC Design - Wo-Tak Wu; Louri, Ahmed (IEEE computer architecture letters, 2016)
The number of cores in a multicore chip design has been increasing in the past two decades. The rate of increase will continue for the foreseeable future. With a large number of cores, the on-chip communication has become a very important design consideration. The increasing number of cores will push the communication complexity level to a point where managing such highly complex systems requires much more than what designers can anticipate for. We propose a new design methodology for implementing a cognitive network-on-chip that has the ability to recognize changes in the environment and to learn new ways to adapt to the changes. This learning capability provides a way for the network to manage itself. Individual network nodes work autonomously to achieve global system goals, e.g., low network latency, higher reliability, power efficiency, adaptability, etc. We use fault-tolerant routing as a case study. Simulation results show that the cognitive design has the potential to outperform the conventional design for large applications. With the great inherent flexibility to adopt different algorithms, the cognitive design can be applied to many applications.